Association of serum vitamin B12 and folate with mortality in incident hemodialysis patients - Soohoo, Melissa; Ahmadi, Seyed-Foad; Qader, Hemn; Streja, Elani; Obi, Yoshitsugu; Moradi, Hamid; Rhee, Connie M.; Kim, Tae Hee; Kovesdy, Csaba P.; Kalantar-Zadeh, Kamyar (Nephrology, dialysis, transplantation, 2017)
Vitamin B12 (B12) and folate are essential vitamins that play important roles in physiological processes. In the general population, many studies have evaluated the association of these vitamins with clinical outcomes, yet this association in hemodialysis (HD) patients remains unclear. We examined the association of serum folate and B12 with mortality in a 5-year cohort of 9517 (folate) and 12 968 (B12) HD patients using Cox models with hierarchical adjustment for sociodemographics, comorbidities, and laboratory variables associated with the malnutrition and inflammation complex syndrome. The associations of baseline B12 and folate (separately) with all-cause mortality were evaluated across five categories of B12 [<400 (reference), 400-<550, 550-<650, 650-<750 and ≥750 pg/mL] and folate [<6.2, 6.2-<8.4, 8.4-<11 (reference), 11-<14.3 and ≥14.3 ng/mL]. The study cohort with B12 measurements had a mean ± standard deviation age of 63 ± 15 years, among whom 43% were female, 33% were African-American, and 57% were diabetic. Higher B12 concentrations ≥550 pg/mL were associated with a higher risk of mortality after adjusting for sociodemographic and laboratory variables. However, only lower serum folate concentrations <6.2 ng/mL were associated with a higher risk of all-cause mortality when adjusted for sociodemographic variables [adjusted hazard ratio (95% confidence-interval): 1.18 (1.03-1.35)]. Higher B12 concentrations are associated with higher all-cause mortality in HD patients independent of sociodemographics and laboratory variables, whereas lower folate concentrations were associated with higher all-cause mortality after accounting for sociodemographic variables. Further studies are warranted to determine the optimal B12 and folate level targets in this population.